KOMUNIKASI PERSUASIF PADA PROGRAM ACARA PENDIDIKAN “YO NGOPI LUK” TVRI BANGKA BELITUNG - Pebri Yanasari (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2021)
One method that can be used by communicators to give influence and effect to the communicant is to use persuasive communication. In this study, researchers analyzed the educational program "yo ngopi luk" at the TVRI Bangka Belitung Public Broadcasting Institute. It is hoped that this research can contribute ideas for readers and the general public and even TVRI Bangka Belitung. The type of research used is qualitative research with a phenomenological approach. The researcher chose to focus on several elements in the “Yo ngopi luk” program by conveying messages in each display of the program, including: (1) Persuader, (2) Persuadee, (3) persuasive Messages, (4) persuasive Channels, (5) Feedback, and (6) Effect. From the results of the analysis of the "yo ngopi luk" educational program, it can be seen that persuasive communication is still considered less successful in influencing the attitudes and mindsets of the people of Bangka Belitung.